Full factorial design assisted RP-UHPLC method development and study of stressed degradation of molnupiravir - Faruk, Omar; Shill, Diponkor Kumar; Lira, Dilshad Noor; Rouf, Abu Shara Shamsur; Kumar, Uttom (Drug Analytical Research, 2026)
To combat the SARS-CoV-2 addition of molnupiravir into the current therapeutic regimen has added new hopes. But currently, not so many analytical methods are available for analyzing molnupiravir. The current study aimed at developing a suitable and efficient RP-UHPLC method for molnupiravir capitalizing full factorial design. The optimized method involved the use of trifluoroacetic acid (0.1%): methanol at a ratio of 65:35 (%, v/v) with fortis diphenyl HPLC column (150 mm x 4.6 mm i.d. [internal diameter], 5 μm particle size). The method was found highly specific (purity index <1.5), linear (0.5-100 μg.mL-1), accurate ( 100%), precise, rugged, and robust (%RSD<2). A stress degradation study exhibited that 0.1N HCl at 100˚C (±1˚C) for 2 hours caused drug degradation crossing its limit (>10%), the drug is extremely susceptible to basic hydrolysis and 0.1N NaOH at room temperature for 1 min caused 65.43% degradation, exposure in 3% H2O2 at 100˚C (±1˚C) for 1 hours caused the drug degradation over 10%, and 5 days of exposure to short wavelength UV light caused 13.16% of drug degradation. The research work successfully developed an efficient and validated method for analyzing molnupiravir in the RP-UHPLC system. Moreover, the degradation study performed will aid in adding integral information related to the stability of the drug molecule.